Cytotoxic, anti-inflammatory, antioxidant, and anti-glyoxalase-I evaluation of chelating substances: In silico and in vitro study - MohammedBashar Al-Qazzan; Qosay Al-Balas; Belal Alnajjar; Violet Kasabri; Yusuf Al-Hiari; Aref Zayed; Rema AlKhateeb; Mohammed Al-Akeedi (PLoS ONE, 2025)
Introduction Glyoxalase I is a crucial target in cancer treatment due to its involvement in detoxifying methylglyoxal. Suppressing the activity of Glyoxalase I has great potential for disrupting the pathways that allow cancer cells to survive, creating a new route for cancer treatment. Methodology This study aims to investigate several substances as inhibitors of glyoxalase-I. After demonstrating their efficacy, additional inquiry will concentrate on assessing their cytotoxic and anti-inflammatory capabilities, yielding significant insights for prospective medicinal uses. The selection of these chemicals as potential Glyoxalase I inhibitors was based on their ability to bind metals, in crucial enzymes. These compounds consist of catechol, dihydroxy, trihydroxy benzene, and functional groups such hydroxamic acid, sulfur, carboxylic acid, amide, and 3-hydroxy-4-pyridone with the aim to suppress Glyoxalase I in vitro. Docking protocol was employed to examine the binding interactions with the active site. These auspicious compounds have been subjected to cytotoxicity assay testing employing Sulforhodamine B in eleven distinct cell lines, as well as anti-inflammatory and antioxidant evaluations. Results Glyoxalase I inhibition revealed that 4-hydroxy-estradiol exhibited the highest efficacy with an IC50 value of 0.226 µM. Trichostatin A demonstrated a significant anti-proliferation effect in colorectal cancer cells (CACO2, HCT116, SW620, HT29) with IC50 values ranging from 14.0 µM to 27.0 µM. Furthermore, it exhibited substantial decreases in viability, ranging from 1.4 µM to 14.7 µM, in cancer cell cultures of skin (A375), lung (A549), prostate (PC3), breast (MCF7 and T47D), and cervical (HeLa). Except for 4-hydroxyestrdiol, the other phytochemicals demonstrated considerable selectivity in reducing the viability of cancer cells in monolayers of colorectal, cervical, mammary, lung, and skin tissues. In comparison to indomethacin and vitamin C, all of the studied natural compounds exhibited excellent anti-inflammatory properties in LPS-primed RAW 264.7 murine macrophages and had moderate antioxidant abilities comparable to ascorbic acid, with IC50 values from 26.0 µM to 99.0 µM. Conclusion Further assessment of molecular action mechanisms and structural betterments/enhancements and/or derivatization of promising potent agents with antiglyoxylase – antiinflammation duality along with differential cytotoxicity and reductive capacities are advisably warranted with appropriately matched downstream in vivo validation modalities.